Tecnología educativa como herramienta innovadora para la enseñanza-aprendizaje, en EGB superior de la Unidad Educativa Imbana. Año lectivo 2023-2024 - Panamito Valdiviezo, Verónica Elizabeth (2024)
Educational technology has proven to be an innovative and effective tool in the field of teaching- learning, because through it, motivating environments are generated that promote the participation and interest of students towards learning to learn, which improves their academic performance, the objective proposed for this research corresponds to: <<Determine how the use of educational technology as an innovative tool, for teaching-learning, affects the students of the upper GBE of the Imbana Educational Unit, during the school year 2023-2024>>. The method used was inductive, which prioritizes the direct observation of the object of study, with a qualitative approach that allowed characterizing the reality of the institution in relation to the implementation of technological tools; it corresponds to diagnostic research; since, through research instruments, it allowed evidencing the skills, knowledge and needs of teachers and students regarding what involves educational technology. Finally, it is concluded that, according to the level of Internet access and electronic devices in the homes of the students surveyed, there is evidence of unequal opportunities for improvement in terms of academic results; on the other hand, the lack of information and updating of teachers prevents them from implementing technology in the PEA; regarding the technological infrastructure of the institution, it is inadequate, Internet service is available only in some classrooms and deficiencies have been identified, such as lack of electronic devices, intermittent connectivity and no technical support.